Socio-demographic patterns of posttraumatic stress disorder in Medellin, Colombia and the context of lifetime trauma exposure. Issue 4 (1st October 2016) - Gaviria, Silvia Lucia; Alarcón, Renato D.; Espinola, Maria; Restrepo, Diana; Lotero, Juliana; Berbesi, Dedsy Y.; Sierra, Gloria Maria; Chaskel, Roberto; Espinel, Zelde; Shultz, James M.
ABSTRACT: Colombia, South America is currently transitioning to post-conflict status following 6 decades of armed conflict. The population has experienced extensive exposures to potentially traumatic events throughout the lifespan. Sources of trauma exposure include the prolonged armed insurgency, narco-trafficking violence, urban gang violence, violent actions of criminal bands, intra-familial violence, gender-based violence, and sex trafficking. Exposure to potentially traumatic events is related to a variety of psychiatric outcomes, in particular, posttraumatic stress disorder. Given this context of lifetime trauma exposure, socio-demographic patterns of posttraumatic stress disorder were explored in a sample of residents of Medellin, Colombia, the nation's second largest city and a nexus for multiple types of trauma exposure.